Study on micro-scale properties of cohesive zone in shale. (15th May 2019) - Dong, Jingnan; Chen, Mian; Jin, Yan; Hong, Guobin; Zaman, Musharraf; Li, Yuwei
Highlights: Multi-scale crack opening displacement is obtained, a small apparatus is made to induce the ongoing subcritical crack within double-cantilever-beam specimen in the environmental scanning electron microscope, by which successive in-situ images of crack propagation are acquired. By comparing experimental results and analytical solutions of micro-scale crack opening displacement, the fitting of cohesive zone models is performed. Several CZM models are compared. Based on numerous observation results, the concept of cohesive-zone-model unit is introduced to provide a better understanding of the essence of cohesive stress. The mechanical properties of cohesive-zone-model unit is simulated using two-dimensional particle flow code. A calibration based on energy release rate is carried out. Abstract: Cohesive fracture model is well known for obtaining a concise interpretation on the underlying mechanism of failure in the near-crack-tip field, especially in concrete and rock materials. In this study, the micro-scale properties of the cohesive zone in brittle shale are investigated. Micro-scale measuring method is designed to capture the crack opening displacement. A small apparatus is developed to induce the ongoing subcritical crack within double-cantilever-beam specimen in environmental scanning electron microscope, by which successive in-situ images of crack propagation are acquired. Micro-scale crack opening displacement of Mode I fracture is either directly measured or measured by digital image correlation method. By comparing experimental results and analytical solutions of micro-scale crack opening displacement, the fitting of cohesive zone models is performed. Based on numerous observations of results, the concept of cohesive-zone-model unit is introduced to provide a better understanding of the essence of cohesive stress. The mechanical properties of cohesive-zone-model unit is simulated using a two-dimensional particle flow code. The simulation results conform to the fitting results. Taking both the fitting and the simulation results into consideration, the traction-separation curve based on cubic polynomial law provides the best interpretation of the micro-mechanical properties of cohesive zone in shale. The introduction of cohesive-zone-model unit gives a better interpretation on the essence of cohesive stress in brittle material with small-scale flaws.